EFEKTIFITAS MEKANISME TATA KELOLA TEKNOLOGI INFORMASI TERHADAP INOVASI TI DAN KINERJA TI - Anwar Fattah; Resad Setyadi (Jurnal Teknologi Informasi dan Pendidikan, 2019)
Information technology supports the achievement of business objectives in the organization. Higher education institutions is a business organization engaged in the field of education, research and devotion to the society in the Know Tridharma College. Effective IT governance ensures the alignment between IT and the business objectives. The study seeks to examin empirically IT governance mechanisms affecting the overall effectiveness of IT governance. In addition, this study examines effective IT governance relationships and IT performance in higher education organizations. The sampling techniques in this study are multi-stage purposeful random sampling. In order, the researchers will incorporate the surveys online. Analyzed by Quantitative Data and method of a Partial Least Squares (PLS-SEM) equation using Smart PLS 3.0. The results obtained from this research show significant positive relationships between effectiveness IT governance and the following mechanisms: IT steering Committee, senior management involvement in IT, and organizational communication systems and relationships between the effectiveness of ITG with IT innovation and IT performance. And insignificant negative relationship between organizational Performance management system and effectiness IT Governance also IT Innovation and IT Performance.